Introduction to solid modeling using SolidWorks® - Howard, William E. (McGraw-Hill / Irwin, 2006)
The text presents solid modeling not just as a communication tool, but as an integral part of the design process. To this end the book explores design intent, the use of solid models in engineering analysis, and introduces techniques from manufacturing such as mold design and sheet metal patterning